Analyze Education and Training Using Marine Engine Simulator at STIP Jakarta Indonesia - Abdul Rachman; Marihot Simanjuntak (STAI Miftahul Ula Nganjuk, 2019)
On this research paper analysis Cadet Engineer, junior engineer, Operational level senior engineer, and management level senior engineer will do experiment using data velocity various scenario at marine engine simulator and then result of experiment will use analysis education and training marine engine simulator for to know correct time. Then analysis has also revealed that the human errors occur for the following reasons: Lack of knowledge on the over all system and fundamental operation, Insufficient confirmation to operation and Incomplete knowledge on the operational sequence. the roles of instructor will be described in order to reduce the cause for such human errors and to enhance the educational performance according implemented and development each them various scenario base on expert justification and reference IMO Standard and SOLAS. kinds various scenario safety procedure for all Engineer with hope to minimalist accident loss of soul at sea. For the purpose of machinery plant operation training by means of Engine Room Simulator (ERS) based on PC, describes the features of human errors by the Incompetence trainees in the marine engine plant operation and shows the necessary improvement in the training in order to decrease such errors from the viewpoint of educational technology. The examination of such data has shown that error occurs mainly by omission error and extraneous act. Further analysis was made on such errors by the trainees engineer to find out the characteristics of errors caused in the process of acquiring procedural knowledge for the operation according implemented development various safety scenario.